Climate Smart Agriculture Country Profile Data - Nyakundi, Fridah Nyabate; Osiemo, Jamleck; Grosjean, Godefroy; Nguyen, Tam Ninh; Girvetz, Evan Hartunian; Jaquet, Stéphanie; Lizarazo, Miguel; Mburu, Rachael; Grey, Sebastian; Röhrig, Felicitas; Giles, James; Nowak, Andreea C.; et al. (Bioversity International and the International Center for Tropical Agriculture, 2020)
This article describes a Climate-Smart Agriculture (CSA) database collected from 34 countries, 16 in Africa, 7 in Asia and 11 in Latin America and the Caribbean (LAC) by the International Center for Tropical Agriculture (CIAT) in collaboration with various stakeholders in respective countries. The dataset is a combination of both quantitative and qualitative data collected via a participatory approach that involved several players from different levels; farmers, input suppliers, processors, traders, policymakers, and donors. Primary data was collected from country experts in interviews, focus group discussions and workshops; a semi-structured survey questionnaire was used to conduct interviews and guide focus group discussions. A structured questionnaire was used to collect data in workshops. Secondary data on various agricultural indicators required for country CSA profiling were accessed via national and global public repositories. The data comprise of CSA practices, CSA scores across the three CSA pillars for selected production systems or value chains, existing climate-related policies at country level, and institutions implementing, overseeing or developing climate policies and interventions. The data shows CSA adoption levels, barriers to adoption and type of farmers using each of the practices the most. Over 1500 experts were interviewed in data collection (2020-05-07)